2022
DOI: 10.3390/rs14040865
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Stratification Method for the Sampling Design of LULC Classification Accuracy Assessment: A Case Study in Beijing, China

Abstract: Spatial sampling design is important for accurately assessing land use and land cover (LULC) classification results from remote sensing data. Spatial stratification can dramatically improve spatial sampling efficiency by dividing the study area into several strata when classification correctness is spatially stratified heterogeneous. By integrating the LULC classification results from different sources and spatial resolutions, a spatial stratification method for spatial sampling of accuracy assessment is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Water bodies were additionally stratified by size and type to ensure that the assessment was representative of the diversity of water bodies present in the study area. Spatial stratification also improves the assessment of the classification accuracy of remote sensing data (Dong et al, 2022 ). Spatial autocorrelation examines how pixels that are close together are more similar than those that are far apart (Karasiak et al, 2022 ), resulting in falsely high precision metrics (Roberts et al 2017 ; Meyer et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Water bodies were additionally stratified by size and type to ensure that the assessment was representative of the diversity of water bodies present in the study area. Spatial stratification also improves the assessment of the classification accuracy of remote sensing data (Dong et al, 2022 ). Spatial autocorrelation examines how pixels that are close together are more similar than those that are far apart (Karasiak et al, 2022 ), resulting in falsely high precision metrics (Roberts et al 2017 ; Meyer et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each sample size was 1024 × 1024 pixels. After gridding the sample area into squares, geospatially stratified and optimized sampling [50][51][52] was used to select sample areas, as shown in the "Sample area selection" in Figure 4. This sampling method yielded representative training samples and reduced the workload of the preparation of the benchmark dataset with annotations.…”
Section: Sample Area Selectionmentioning
confidence: 99%
“…They found that the WorldCover dataset showed the highest overall accuracy, but FROM-GLC10 posed advantages in the classes of farmland, water, and built-up areas. Nevertheless, these efforts are either focused on assessing the overall accuracy of the product [17][18][19][20][21][22] or are class-specific [23][24][25][26]. There is a lack of evaluations on forest-related materials to better understand and use them.…”
Section: Introductionmentioning
confidence: 99%